Rethinking the web as a personal archive - Lindley, Siân; Marshall, Cathy; Banks, Richard; Sellen, Abigail; Regan, Tim (Proceedings of the 2013 international conference on World Wide Web (WWW 2013), 2013)
In recent years the Web has evolved substantially, transforming from a place where we primarily find information to a place where we also leave, share and keep it. This presents a fresh set of challenges for the management of personal information, which include how to underpin greater awareness and more control over digital belongings and other personally meaningful content that is hosted online. In the study reported here, we follow up on research that suggests ownership and control can be reinforced by federating online content as a virtual, single store; we do this by conducting interviews with 14 individuals about their Web-based content. Participants were asked to give the researchers a tour of online content that is personally meaningful to them; to perform a search for themselves in order to uncover additional content; and to respond to a series of design envisionments. We examine whether there is any value in an integrated personal archive that would automatically update and serve firstly, as a source of information regarding the content within it (e.g. where it is stored, who has the rights to it), and secondly, as a resource for crafting personal artefacts such as scrapbooks, CVs and gifts for others. Our analysis leads us to reject the concept of a single archive. Instead, we present a framework of five different types of online content, each of which has separate implications for personal information management.